LITHOTYPE AND CHEMICAL CHARACTERISTICS OF THE SOUTH WALKER CREEK COALS, BOWEN BASIN, AUSTRALIA - A K Permana; C R Ward; L W Gurba (Jurnal Geologi dan Sumberdaya Mineral, 2013)
Lithotype analysis is very useful for guidance in microscopic analysis, predominantly maceral studies. However, the lithotype analysis may also contribute to identify mineral matter occurrence and chemical characteristics. The South Walker Creek coal occurs in a single seam 10.5 to 14 m in thickness and is dominated by dull and bright (40-60% bright), and dull with numerous bright bands (10-40% bright) lithotypes, along with minor dull (< 1% bright) coal. In vertical profile the lithotype content of the seams show an irregular pattern from the top to the bottom. The bright and banded coal tends mainly to occur in or around the middle of the seam. Carbonaceous shale and claystone are the most common clastic bands. The occurrence of clastic dirt bands is mostly associated with the duller plies in the coal seam. Duller lithotypes are mostly associated with a high proportion of inertinite and mineral matter content which is suggests the coal was formed in deep-water conditions. Proximate and fixed carbon analysis shows that the coal seam has relatively higher grade in the middle of the seam and decreases markedly in the top and bottom of the seam. This indicates that the middle of the seam associated with the bright and banded coal lithotype, however in the top and bottom of the seam in association with the duller plies or claystone and carbonaceous shale. This paper is developed from MSc thesis at the University of New South Wales, Australia.Keywods: coal lithotype, chemical characteristics, South Walker Creek, Bowen Basin